Respect, Effective Communication, Family Support and Motivation on Patient Compliance to Improve Drug-Resistant Tuberculosis - Manurung, Sarah; Pamungkas, Rian Adi; Wekadigunawan, Cri Sajjana Prajna (Alta Dharma Publisher, 2025)
Background: The treatment compliance of rifampicin-resistant tuberculosis (TB RO) patients in Indonesia remains suboptimal, with a therapy success rate of only 51%. Various psychosocial determinants such as perceived respect from healthcare providers, effective communication, and family support are believed to influence patients’ adherence, with motivation serving as a potential psychological mediator. Objective: This study aimed to examine the effects of respect, effective communication, and family support on treatment compliance among TB RO patients, with motivation as an intervening variable. Method: A quantitative approach using a cross-sectional design was applied. The study population comprised 116 TB RO patients treated at Tangerang City Hospital, and 90 respondents were selected using Slovin’s formula with simple random sampling. Data were collected through structured questionnaires and analyzed using SmartPLS 4. Results: Respect from healthcare providers did not significantly affect treatment compliance (T=0.533; p=0.594). Effective communication showed no direct influence on compliance, but had a significant indirect effect through motivation (T=3.349; p=0.001). Family support had a significant direct effect on compliance (T=2.058; p=0.040) and also influenced compliance indirectly via motivation. Motivation acted as a mediator between effective communication and family support with compliance, but did not mediate the effect of respect. Conclusion: Family support emerged as the most influential factor in improving treatment compliance among TB RO patients. Strengthening patients’ motivation through enhanced respect and effective communication from healthcare providers is recommended to improve adherence outcomes